PERBEDAAN HASIL DALAM MENYELESAIKAN SOAL PELUANG DITINJAU BERDASARKAN GENDER - Siti Nursayyidah; Ratni Purwasih (IKIP Siliwangi, 2020)
This research is a qualitative descriptive wich aims to find out the differences in the results in solving the material opportunity questions based on gender. The population in this research is all students of class IX in one private junior high school in Cimahi with a sample of 4 female students and 6 male students. The instrument used consists of four written test questions in the form of descriptions on the opportunity material. The data analysis in this study is to calculate the score of the answers, add up the results of each question, calculate the average questions, and interpret the results of the students’ difficulties based on the assessment scale. The results showed that gender differences have an effect on solving math problems. Female students are more dominant in answering and solving math problem clearly than male students.